Enhancing Lecturer Competence In Developing Case Method-Based Semester Learning Plans - Laode Muh ZulFardin Syah; Mclean HY; Anwar Wahid; Cita St. Munthakhabah R; Zam’ah (Information Technology Education Journal, 2025)
This study provides an in-depth examination of the implementation and impact of a workshop designed to enhance lecturers' competence in developing innovative Semester Learning Plans (RPS) based on the Project/Case Method. Amidst the demands of the Merdeka Belajar Kampus Merdeka (MBKM) policy, which prioritizes active, student-centered learning, lecturers' ability to design authentic and applicable learning experiences has become a crucial factor in improving the quality of higher education and equipping graduates with relevant skills. The workshop, titled "Building a Project and Case Method-Based RPS for Active and Meaningful Learning," was organized by the Information Technology Education Study Program at the University of West Sulawesi as a strategic response to this need. The event was conducted as an intensive face-to-face session on August 6, 2025, featuring an expert speaker in curriculum design and pedagogy. A total of 15 lecturers from the Faculty of Teacher Training and Education (FKIP) registered and actively participated until the conclusion. The workshop's success was evaluated not only through feedback but also directly through the practice of drafting an RPS, which served as the main performance indicator. Participants were guided to apply robust theoretical frameworks, such as the principle of constructive alignment, to ensure coherence between Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and Sub-CPMKs. Furthermore, the application of the revised Bloom's Taxonomy was a primary focus for formulating challenging learning objectives that foster Higher-Order Thinking Skills (HOTS). The study's results indicate that this training approach, which combines theory with direct practice, is highly effective. Participants successfully produced initial drafts of RPS that integrated project and case study methods, demonstrating a significant improvement in their understanding and skills. This study concludes that the professional development of lecturers through targeted workshops is a critical investment for pedagogical transformation, which in turn directly contributes to enhancing the quality of the learning process and achieving institutional academic excellence.